2010
DOI: 10.1002/clen.200900307
|View full text |Cite
|
Sign up to set email alerts
|

Free Amino Acids Content in Some Halophytes under Salinity Stress in Arid Environment, Jordan

Abstract: The variation in free amino acids concentration was examined in halophytes under salt stress conditions during spring and autumn in an arid environment, Jordan. The experiment was conducted in the southern region of the Jordan valley, using four different halophytes namely: Atriplex halimus, Atriplex nummularia, Tamarix aphylla L., and Portulaca oleracea L. Free amino acid concentrations showed changeable patterns under salinity stress conditions compared to the non-stress (control) with respect to plant speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 69 publications
1
16
0
Order By: Relevance
“…The identification of untargeted metabolites and ROS scavenging activities under control and stress conditions reveal potential of the plant to be used as functional food and provide useful insights into the metabolic responses and metabolite constituents of this halophyte. The composition of amino acids was studied in some halophytes, and a variable pattern was detected under salt-stress condition (Nasir, Batarseh, Abdel-Ghani, & Jiries, 2010). In the present study, a higher content of essential and sulphur-rich amino acids was found in plant ( Fig.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The identification of untargeted metabolites and ROS scavenging activities under control and stress conditions reveal potential of the plant to be used as functional food and provide useful insights into the metabolic responses and metabolite constituents of this halophyte. The composition of amino acids was studied in some halophytes, and a variable pattern was detected under salt-stress condition (Nasir, Batarseh, Abdel-Ghani, & Jiries, 2010). In the present study, a higher content of essential and sulphur-rich amino acids was found in plant ( Fig.…”
Section: Discussionmentioning
confidence: 93%
“…A high content of sulphur-rich amino acids (cysteine and methionine) was detected, because of the disruption of the sulphur bonds and release of these amino acids under stress. Previously, it was found that the amino acid content increased in Atriplex halimus, Portulaca oleracea and Tamarix aphylla with salinity during spring and autumn seasons (Nasir et al, 2010). It was observed that accumulation of free amino acids not only provides osmotic adjustment, but also involves maintenance of cell-membrane integrity and stability under stress conditions (Tuteja, Gill, & Tuteja, 2011).…”
Section: Discussionmentioning
confidence: 96%
“…Although high K + /Na + selectivity in plants under saline conditions is considered as one of the selection criteria for salt tolerance 4, 19, the accumulation of osmotic adjustments (Na + and K + ) into the vacuole is also a salt tolerance mechanism for some halophytes such as S. salsa 18 and Cakile maritime 29. Furthermore, some other osmoregulators such as proline and amino acids can also be accumulated by plants 30. Based on this mechanism, some researchers stated that the plantation of salt tolerant plants such as halophytes in saline soils showed an effective decline in soil salinity 30.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is not recommended for a country, such as Jordan, with scarce water resources. Biological methods, such as salt tolerant plants (halophytes) and certain bacterial strains, were reported to be effective in removing salts from the root zone [2,7]. Poor irrigation water quality along with saline-sodic soil has reduced plant yield and represents a serious threat to soil productivity.…”
Section: Introductionmentioning
confidence: 99%